2018
DOI: 10.1007/s10616-018-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of human telomerase reverse transcriptase (hTERT) expression by BIBR1532 in human glioblastoma LN18 cells

Abstract: Increased telomerase activity can be blocked by targeting the hTERT activity at both RNA and catalytic subunits. Various inhibitors had been used to regulate hTERT activity in glioblastoma cell lines and showed promising results. The present study hypothesized that the telomerase specific inhibitor BIBR1532 can effectively down-regulate the telomerase activity in LN18 glioblastoma cell line. LN18 glioblastoma cell line was treated with various concentrations of BIBR1532 at different time intervals. MTT assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Therefore, we investigated whether p53 acted downstream of c-Myc and TERT in sensory neurons to control axon regeneration. Indeed, the specific TERT inhibitor BIBR1532, which has been shown to reduce the protein level of TERT (Lavanya et al, 2018), also led to reduced p53 level in sensory neurons (Fig. 8 A, B), indicating that p53 was regulated by the c-Myc-TERT signaling in sensory neurons.…”
Section: P53 Is Necessary and Sufficient For Supporting Sensory Axon mentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, we investigated whether p53 acted downstream of c-Myc and TERT in sensory neurons to control axon regeneration. Indeed, the specific TERT inhibitor BIBR1532, which has been shown to reduce the protein level of TERT (Lavanya et al, 2018), also led to reduced p53 level in sensory neurons (Fig. 8 A, B), indicating that p53 was regulated by the c-Myc-TERT signaling in sensory neurons.…”
Section: P53 Is Necessary and Sufficient For Supporting Sensory Axon mentioning
confidence: 89%
“…One potential explanation is that in postmitotic neurons TERT is localized in mitochondria to reduce oxidative stress and protect neurons from apoptosis (Liu et al, 2018). Functionally, inhibition of TERT with a specific pharmacological inhibitor BIBR1532 (Lavanya et al, 2018) impaired regenerative axon growth of sensory neurons in a dose-dependent manner without any toxic effects on neuronal survival (Fig. 4G-I ).…”
Section: Tert Functions To Regulate Sensory Axon Regeneration In Vitrmentioning
confidence: 99%
“…Because TERT protein has several non‐canonical functions, its increase could attenuate the detrimental effects induced by PA on cell death. Taking this into account, we aimed to evaluate the role of TERT in T98G cells using a chemical compound (BIBR1532), which is known to inhibit telomerase protein via a reduction of gene and protein expression . Our results suggest that telomerase was involved in the protection by tibolone against cell death induced by PA.…”
Section: Discussionmentioning
confidence: 99%
“…BIRB1532 induces an inhibition of telomerase activity by interacting with a motif involved in DNA binding . Moreover, it has been observed that this compound is able to reduce TERT gene and telomerase protein expression …”
Section: Methodsmentioning
confidence: 99%
“…There have been sufficient cellular activity data to indicate that BIBR1532 has an inhibitory effect on telomerase in human cancer cells with different histological origin, and it can result in progressive shortening of telomere and inhibition of cell proliferation in vitro and in vivo. Cell‐free experiments showed that telomerase inhibition by BIBR1532 was dose‐dependent (IC 50 = 100 nM in vitro) . At concentrations well above this IC 50 , BIBR1532 has no inhibitory effect on DNA polymerase, RNA polymerase, and HIV‐RT probably because HIV‐RT does not have the FVYL motif.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%